For this case, we must find an expression equivalent to:
![\frac {-9x ^ {- 1} y ^ {- 9}} {- 15x ^ 5y ^ {- 3}}](https://tex.z-dn.net/?f=%5Cfrac%20%7B-9x%20%5E%20%7B-%201%7D%20y%20%5E%20%7B-%209%7D%7D%20%7B-%2015x%20%5E%205y%20%5E%20%7B-%203%7D%7D)
By definition of power properties we have:
![a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}](https://tex.z-dn.net/?f=a%20%5E%20%7B-%201%7D%20%3D%20%5Cfrac%20%7B1%7D%20%7Ba%20%5E%201%7D%20%3D%20%5Cfrac%20%7B1%7D%20%7Ba%7D)
Rewriting the previous expression we have:
The "-" are canceled and we take into account that:
![\frac {9} {15} = \frac {3} {5}](https://tex.z-dn.net/?f=%5Cfrac%20%7B9%7D%20%7B15%7D%20%3D%20%5Cfrac%20%7B3%7D%20%7B5%7D)
So:
![\frac {3} {5x^5 * x ^ 1 *y ^ 9* y ^ {- 3}} =](https://tex.z-dn.net/?f=%5Cfrac%20%7B3%7D%20%7B5x%5E5%20%2A%20x%20%5E%201%20%2Ay%20%5E%209%2A%20y%20%5E%20%7B-%203%7D%7D%20%3D)
According to one of the properties of powers of the same base, we must put the same base and add the exponents:
![\frac {3} {5x ^ {5 + 1} * y ^ {9-3}} =\\\frac {3} {5x ^ 6 * y ^ 6}](https://tex.z-dn.net/?f=%5Cfrac%20%7B3%7D%20%7B5x%20%5E%20%7B5%20%2B%201%7D%20%2A%20y%20%5E%20%7B9-3%7D%7D%20%3D%5C%5C%5Cfrac%20%7B3%7D%20%7B5x%20%5E%206%20%2A%20y%20%5E%206%7D)
Answer:
![\frac {3} {5x ^ 6 * y ^ 6}](https://tex.z-dn.net/?f=%5Cfrac%20%7B3%7D%20%7B5x%20%5E%206%20%2A%20y%20%5E%206%7D)
Option B
112/2=56 (sum of both lengths)
4x=56
x=14
length=42
width=14
Answer:
its gonna be -4
Step-by-step explanation:
Yes, I do think that inequalities or equations are used more in everyday life.